Venous Malformation: update on etiopathogenesis, diagnosis & management - Dompmartin, Anne (2010)
The aim of this review was to discuss the current knowledge on etiopathogenesis, diagnosis and therapeutic management of venous malformations. Venous malformations (VMs) are slow-flow vascular anomalies. They are simple, sporadic or familial (cutaneo-mucosal venous malformation or glomuvenous malformations), combined (e.g. capillaro-venous, capillaro-lymphaticovenous malformations) or syndromic (Klippel-Trenaunay, Blue Rubber Bleb Naevus and Maffucci). Genetic studies have identified causes of familial forms and of 40% of sporadic VMs. Another diagnostic advancement is the identification of elevated D-dimer level as the first biomarker of venous malformations within vascular anomalies. Those associated with pain are often responsive to Low Molecular Weight Heparin which should also be used to avoid disseminated intravascular coagulopathy secondary to intervention, especially if fibrinogen level is low. Finally, development of a modified sclerosing agent, ethylcellulose–ethanol, has improved therapy. It is efficient and safe, and widens indications for sclerotherapy to sensitive and dangerous areas such as hands, feet and periocular area.